Essays on growth and economic policy - Antunes, António (2022)
The first two chapters of this thesis deal with public finance in an intertemporal optimizing model, in the tradition of Ramsey. The third is on the impact of informal markets and corruption on growth, and the last on the convergence of a small open economy in the world context. The first two chapters deal with two complementary but largely neglected questions: optimal tax and expenditure structures. The first deals with those questions in an optimizing model with or without intertemporal consistency. The second makes a contribution for the difficult question of the optimal government size given the basic structure of the economy. In the first chapter, we arrive at a generalized taxation benefit principle, which states that in general the tax structure is not independent from the planned pattern of public spending. We also demonstrate that asymptotic tax rates on labor and capital income are zero only if consumption taxes can be used to collect the full amount of resources needed to finance public expenditure, which is endogenously determined. This result indicates that, contrary to models with isoperimetric budget constraints, under a fiscal constraint such as the balanced -budget rule, consumption taxation is superior to factor income taxation. If consumption taxes are constrained, and plans have to be intertemporally consistent, none of the asymptotic tax rates is in general zero. In the second chapter, we study the effects of integrating preferences for public services and productive public investment in an optimal growth model. We identify the basic parameters that are relevant to determine the optimal size of the government. We estimate that a switch from current to optimal policies would yield welfare gains well below the values reported in the literature. The third chapter builds on existing models regarding the effects of corruption and informal markets on economic growth, and extends them to fully decentralized settings. Firms in the formal sector are able to buy patents abroad and engage in Cournot competition. Formal firms pay taxes over their net sales margin. Informal firms are able to imitate goods produced by formal firms at negligible cost. However, they have no access to legal protection, law enforcement or other public services provided by the government. We conclude that, for arbitrary tax rates, free entry in the formal market may be conducive to economic stagnation. Due to the existence of informal markets, the various tax rates cannot influence the total market size. They only affect the size of the formal sector. Moreover, if the government wants to maximize welfare, the design of the fiscal system should take into account informal markets, administrative structure, and fiscal instruments available. We also argue that large public sectors may be the effect of an inefficient administration rather than the consequence of widespread corruption. The fourth chapter is about the effects on growth of the technology that is embedded in imported investment goods. The embedded technology operates through an externality in the production of human capital. To our knowledge, this "engine of growth" is seldom approached in the literature. We arrive at the conclusion that agents consume too many foreign goods from a social perspective, and invest too little. We also conclude that a high steady-state growth rate of the world economy is associated with a high exports share of output, provided that certain restrictions on preferences are satisfied. By approximating the model's dynamic equations around the steady state, we typically obtain relatively slow convergence rates.